Youth Perception and the Effects of Disciplinary Action Implemented in School - Noni Harianti Junaidi; Lisa Richard; Nur Hafizah Busrah (RIRAI Publisher, 2021)
The disciplinary problem in school has become one of the popular issues in Malaysia. The purpose of this study is to describe youth perceptions and the effects of disciplinary action implemented in school. It intends to achieve three main objectives which are to identify the perceptions of youth towards disciplinary action practice in school, to examine the effects of disciplinary action practice, and to make comparisons between gender and its acceptance towards disciplinary action in school. Data collection had been carried out using a quantitative approach through convenient sampling. There were 260 questionnaires distributed to respondents from the diploma and degree students under the Faculty of Administrative Science & Policy Studies at MARA University of Technology (UiTM) in Kota Samarahan. Findings showed that most youths agreed on the good perception of the disciplinary action implemented in school. However, there were also respondents who had given some opinions and recommendations. Nevertheless, only some of the students tend to access aggressive solutions. This study also did a comparison between gender and its acceptance toward disciplinary action in school. However, finding indicated there was no difference of acceptance between genders.